Analysis of the Impact of Adding an Interposed Transformer on Distribution Transformer Protection Components on the Gontang Feeder at PT. PLN (Persero) ULP Mattoanging - Reski Anugerah; Muhammad Yusuf Mappeasse; Andi Imran (Fakultas Teknik Universitas Negeri Makassar, 2026)
This research aims analyze of adding an inserted (interposing) transformer on the loading level of the distribution transformer as well as the performance and suitability of protective components, including Fuse Cut Out (FCO), No Fuse Breaker (NFB), and NH Fuse, on the Gontang feeder of PT PLN (Persero) ULP Mattoanging. The research method employed is quantitative descriptive, using a combination of manual calculations and simulation approaches with ETAP and Digsilent PowerFactory software, with data collected through documentation, observation, and interviews. The results indicate that the main transformer GT 0234, prior to the addition of the inserted transformer, experienced a loading level of approximately 92%, which is classified as overload as it exceeds the safe transformer loading limit of 80%. After the installation of the inserted transformer GT 0870 with a capacity of 160 kVA, the loading of the main transformer decreased to approximately 47–48%, while the loading of the inserted transformer ranged between 56–57%, resulting in normal operating conditions. The manual calculation results are consistent with the simulation results obtained from ETAP and Digsilent PowerFactory. Furthermore, the current flowing through the protective components decreased after the addition of the inserted transformer and remained within safer operating limits; however, discrepancies were still found between the installed protective component ratings and the results of the calculations and simulations. Therefore, an evaluation and adjustment of the protective component ratings are required to improve protection coordination and system reliability.